Dynamic temperature measurements on a thermally activated self-healing ionomer. (January 2014) - Haase, Thomas; Rohr, Ingmar; Thoma, Klaus
An ionomer, which is able to self-heal the damage after ballistic impact of a projectile, was studied using dynamic puncture tests. A temperature increase in this polymer is a fundamental part of the self-healing process. Therefore, the temperature during the puncture tests was measured using embedded thermocouples. These adiabatic temperature measurements allow for some first conclusions about the processes that are involved in the heating of the material during an impact process.